2016
DOI: 10.1016/j.bbacli.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma metabolites and glucose homeostasis during omega-3 polyunsaturated fatty acid supplementation in women with polycystic ovary syndrome

Abstract: BackgroundBoth fish (FO) and flaxseed oils (FLX) are n-3 polyunsaturated fatty acids (PUFA). Fish oil contains long chain while FLX contains essential n-3 PUFA. We demonstrated that FO altered insulin secretion and resistance in polycystic ovary syndrome (PCOS) women but FLX did not. Surprisingly, the effects of FO were similar to those of the n-6 PUFA-rich soybean oil (SBO). Since increased branched chain (BCAA) and aromatic amino acids (AA) affect insulin secretion and resistance, we investigated whether FO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Nine of the 45 trials were performed exclusively on women and nine on men , and the remaining trials included both sexes; however, three studies did not mention sex composition of participants . Eligible studies were published between 1995 and 2016, and most of them were conducted in the USA , Canada , Iran and Brazil . The remaining studies were conducted in China , Australia , Greece , Germany , Denmark , Romania India and Japan .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine of the 45 trials were performed exclusively on women and nine on men , and the remaining trials included both sexes; however, three studies did not mention sex composition of participants . Eligible studies were published between 1995 and 2016, and most of them were conducted in the USA , Canada , Iran and Brazil . The remaining studies were conducted in China , Australia , Greece , Germany , Denmark , Romania India and Japan .…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the 45 trials were performed exclusively on women (31,38,41,43,45,48,51,57,75) and nine on men (40,44,46,54,56,63,65,70,74), and the remaining trials included both sexes; however, three studies did not mention sex composition of participants (58,67,68). Eligible studies were published between 1995 and 2016, and most of them were conducted in the USA (31,37,38,46,52,57,60,61,66,70,75), Canada (22,23,(41)(42)(43)48,50,67), Iran (21,59,69,71,73) and Brazil (24,39,44,45,49). Th...…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism is that delivery of excess fatty acids along with branched chain amino acids to the mitochondria interferes with glucose utilization 30 31. In an earlier study we had demonstrated that polyunsaturated fatty acids (3 g/day) alter plasma amino acids and their metabolism in humans 32. Endogenous hypertriglyceridemia also increases fatty acid delivery to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…16,[108][109][110][111] Mainly, most of the clinical trials of PUFA supplementation were of short duration (6-12 weeks) and the supplementation dose ranged between 2 and 4 g PUFAs per day. [108][109][110][112][113][114][115][116][117][118] A recent meta-analysis of eight clinical trials with a total of 298 females with PCOS showed a slight reduction in serum total testosterone levels following n-3 PUFA supplementation among females with PCOS, without significant impact on SHBG and DHEAS levels. 119 Results from a cross-sectional study showed that increased plasma n-6 PUFAs or increased n-6:n-3 PUFA ratio was associated with greater circulating androgen concentrations, whereas increased long-chain n-3 PUFA in plasma was associated with decreased blood lipids in women with PCOS.…”
Section: Pufa and Pcosmentioning
confidence: 99%